Landscape and dynamics of single tumor and immune cells in early and advanced‐stage lung adenocarcinoma. Issue 3 (9th March 2021) - Chen, Zhencong; Huang, Yiwei; Hu, Zhengyang; Zhao, Mengnan; Li, Ming; Bi, Guoshu; Zheng, Yuansheng; Liang, Jiaqi; Lu, Tao; Jiang, Wei; Xu, Songtao; Zhan, Cheng; et al.
Abstract: Background: Lung adenocarcinoma (LUAD) patients with different American Joint Committee on Cancer stages have different overall 5‐year survival rates. The tumor microenvironment (TME) and intra‐tumor heterogeneity (ITH) have been shown to play a crucial role in the occurrence and development of tumors. However, the TME and ITH in different lesions of LUAD have not been extensively explored. Methods: We present a 204, 157‐cell catalog of the TME transcriptome in 29 lung samples to systematically explore the TME and ITH in the different stages of LUAD. Traditional RNA sequencing data and complete clinical information were downloaded from publicly available databases. Results: Based on these high‐quality cells, we constructed a single‐cell network underlying cellular and molecular features of normal lung, early LUAD, and advanced LUAD cells. In contrast with early malignant cells, we noticed that advanced malignant cells had a remarkably more complex TME and higher ITH level. We also found that compared with other immune cells, more differences in CD8+/CTL T cells, regulatory T cells, and follicular B cells were evident between early and advanced LUAD. Additionally, cell‐cell communication analyses, revealed great diversity between different lesions of LUAD at the single‐cell level. Flow cytometry and qRT‐PCR were used to validate our results. Conclusion: Our results revealed the cellular diversity and molecular complexity of cell lineages in different stages of LUAD. We believe our research, which serves as a basic framework and valuable resource, can facilitate exploration of the pathogenesis of LUAD and identify novel therapeutic targets in the future. Abstract : Our study comprehensively studied the tumor microenvironment (TME)and intra‐tumor heterogeneity (ITH) in different stages of LUAD by both scRNA‐seq and bulk RNA‐seq analyses. Based on these high‐quality cells derived from different tissues, our results revealed the cellular diversity and molecular complexity of cell lineages in different stages of LUAD. This study, which serves as a basic framework and valuable resource, can facilitate exploration of the pathogenesis of LUAD and identify novel therapeutic targets in the future.